2021
DOI: 10.3390/children8110997
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Polyps in Children: The Early Origins of a Challenging Adulthood Condition

Abstract: Nasal polyps (NPs) are benign inflammatory masses causing chronic nasal obstruction, usually associated with underlying chronic rhinosinusitis (CRS), which are rarely reported in childhood. The interest in NPs has recently increased due to new therapeutic options, namely biological agents, such as dupilumab, and an update of the European position paper on this topic was released in 2020, providing a detailed classification for these lesions and also discussing diagnostic and therapeutic approaches also in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
0
9
0
1
Order By: Relevance
“…In the pediatric population, nasal polyps usually represents red flags indicating underlying systemic diseases, such as Cystic Fibrosis (CF), Primary Ciliary Dyskinesia (PCD) and immunodeficiencies. 30 A study with 4044 children diagnosed with CRS found that the prevalence of cystic fibrosis was 4.1% of immune system disorder was 12.3% and 0.2% had primary ciliary dyskinesia. 31 …”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, nasal polyps usually represents red flags indicating underlying systemic diseases, such as Cystic Fibrosis (CF), Primary Ciliary Dyskinesia (PCD) and immunodeficiencies. 30 A study with 4044 children diagnosed with CRS found that the prevalence of cystic fibrosis was 4.1% of immune system disorder was 12.3% and 0.2% had primary ciliary dyskinesia. 31 …”
Section: Discussionmentioning
confidence: 99%
“…These are frequently associated with respiratory diseases, including AR and asthma, cystic fibrosis, AERD, and chronic rhinosinusitis (CRS). NPs are relatively common in the adult population, and they are rare in children under ten years old [ 64 ]. Exosomes are epithelial-derived vesicles containing conserved proteins representative of their parent cell and are secreted by all cell types into almost all body fluids, including nasal mucus [ 65 ].…”
Section: Proteomics Approaches In Respiratory Allergymentioning
confidence: 99%
“…Laser is an acronym for light amplification by stimulated emission of radiation, which originally described the process; however, it is currently used to describe both the light fascicle and the apparatus ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) with nasal polyps (CRSwNP) is presented in ancient texts dating back almost 4,000 years; however, it is still a pathology that is not fully understood and does not have a definitive therapeutic option ( 5 ). Currently, the most used treatment options are intranasal corticosteroids and ESS, with a high recurrence rate due to the preponderance of atopic origin in the majority of nasal polyp cases ( 1 ).…”
Section: Introductionmentioning
confidence: 99%